2011
DOI: 10.2527/jas.2010-3198
|View full text |Cite
|
Sign up to set email alerts
|

The effect of increasing amount of glucogenic precursors on reproductive performance in young postpartum range cows1

Abstract: Supplementing CP and propionate salts (PS) may improve economic returns in young range beef cows by increasing the dietary supply of glucogenic precursors. A 3-yr study conducted at Corona Range and Livestock Research Center (Corona, NM) from February to mid-July in 2005 (n = 80), 2006 (n = 81), and 2007 (n = 80) evaluated days to first estrus, calf weaning weight, BW change, and metabolic responses in 2- and 3-yr-old postpartum cows grazing native range. Cows were individually fed one of three 36% CP suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
0
14
0
1
Order By: Relevance
“…The nutrient supply of grasslands during the winter is insufficient to meet the requirements of the growing fetus in the last third of the pregnancy period, causing a negative energy balance that continues during early postpartum due to the demand for milk production (Bell, 1995;Astessiano et al, 2013). The negative energy balance is evidenced by a decrease in body condition score (BCS) and endocrine changes, such as an increase in non-esterified fatty acids (NEFA) and a decrease in glucose and insulin, which have a negative impact on follicle growth and ovulation (Wiltbank, 1970;Mulliniks et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The nutrient supply of grasslands during the winter is insufficient to meet the requirements of the growing fetus in the last third of the pregnancy period, causing a negative energy balance that continues during early postpartum due to the demand for milk production (Bell, 1995;Astessiano et al, 2013). The negative energy balance is evidenced by a decrease in body condition score (BCS) and endocrine changes, such as an increase in non-esterified fatty acids (NEFA) and a decrease in glucose and insulin, which have a negative impact on follicle growth and ovulation (Wiltbank, 1970;Mulliniks et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although the level of milk production and insulin resistance has been primarily studied in dairy cows, increasing selection for milk production may increase insulin resistance and metabolic challenges for beef cows, especially young, growing 2-and 3-yr-old cows by partitioning nutrients away from growth and reproduction towards milk. Increasing insulin resistance and milk production will ultimately increase mobilization of body reserves and lower reproductive performance (Mulliniks et al, 2011). For instance, Hunter and Magner (1988) compared formaldehyde-treated casein-supplemented heifers with nonsupplemented heifers.…”
Section: Genetic Selection To Increase Metabolic Efficiencymentioning
confidence: 99%
“…For example, Waterman et al (2007) reported as forage quality declines, tissues become less responsive to insulin, resulting in longer glucose half-life. In addition, enhanced energy metabolism in young range cows identified by faster glucose and acetate clearance rates has been reported to increase reproductive performance in beef cows (Waterman et al, 2006;Mulliniks et al, 2011). Therefore, during key physiological periods such as late gestation and early lactation when nutrient requirements increase and cattle are often grazing limited nutrients supplementation strategies could target improving energy utilization of both forage (i.e.…”
Section: Strategic Supplementation To Increase Metabolic Flexibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Data were compiled from 3 independent studies that spanned from 2000 to 2007 (Endecott et al, 2005;Waterman et al, 2006;Mulliniks, 2008;Mulliniks et al, 2011) but with similar designs. Data were compiled from 3 independent studies that spanned from 2000 to 2007 (Endecott et al, 2005;Waterman et al, 2006;Mulliniks, 2008;Mulliniks et al, 2011) but with similar designs.…”
Section: Study Sitementioning
confidence: 99%